EXPERIENCE OF SUBJECTIVE IDENTITY: CASE OF STUDENTS PARTICIPATING IN EXCHANGE PROGRAMS - BALTUŠNINKAITĖ, Rūta; SONDAITĖ, Jolanta (Socialinė teorija, empirija, politika ir praktika, 2016)
The essence of psychological identity is the sense of unity and meaning. The meaning made up by rethinking past experience creates the sense of unity, continuity and meaning in your life. The aim of the research is to analyse how students who participated in exchange programs construct their subjective identity at personal, relational and collective levels. Research was conducted with 2 focus groups (11 students) using narrative research and meaning-making analysis. The results show that multicultural experience changes not only students’ behaviour at all three levels of identity, but it also has a wider influence on their lives and future plans. Students found that they have a vast variety of possibilities and freedom to choose, that they are responsible for their decisions and behaviour. Students perceive the significance of family and friends; relations with relatives had become closer and more genuine, and more liberal with teachers. Students understood that they have the capability to make changes and improve relations with others. Multicultural experience stimulates students’ interest in their own culture, history and increases empathy for foreigners in Lithuania. They found which culture they prefer and why. Research results may be useful for social workers, counselors, and other personnel working with participants of exchange programs. It is important to draw attention to three main aspects of identity (personal, relational, collective) and help participants to integrate these aspects into a holistic identity experience to enable the sense of unity and meaning in their life. In order to prevent adaptation difficulties of returned students, it is also important to relate their subjective identity with personal growth, goals and future potentiality.